Environmental transport studies of components of an insensitive high explosive formulation in soil - Paula, Priscila Simões Teixeira Amaral (2018)
The use of explosives is likely to contaminate soil and groundwater during military training. New insensitive explosive formulations including Insensitive High Explosives (IHEs) are being brought into service as replacements for conventional explosives with the aim to increase 2 safety in handling, transportation and use . Studies on transport of those new formulations are needed since their impact and possible damages to the environment are not well understood. Evaluation on transport through two UK soil types including sand and loam soil was carried out in six vertical s oil columns which were artificially contaminated with Insensitive High Explosive (IHE) formulation containing 3 - nitro - 1,2,4 - triazol - 5 - one (NTO), 2,4 dinitroanisole (DNAN) and 1,3,5 - t rinitro - 1,3,5 - triazinane (RDX) . The columns were watered for six consecutive weeks and t he watering regime was equivalent to the average yearly in England Southwest and South Wales rainfall. The water leachate collected during the six - week experiment was analysed by using High Performance Liquid Chromat ography (HPLC) . Both soil types showed different breakthrough time in the leachate for all IHE components . The accumulated percentage of recovered explosives from sand column leachates we re 99.08 ±17.55 for NTO, 18.98 ± 4.14 for DNAN over a 6 - week period . In contrast, loam soil showed a different behaviour of recovering from leachates. The accumulated percentage of recover ing for NTO w as 0.16 ± 0.07 , 0.64 ± 0.01 and 2.25 ± .75 for DNAN and RDX respect i vel y . Th e results show ed that the soil characteristics affect the transport of explosive through soil rat her than the solubility , suggesting degradation of NTO and DNAN in soil with higher organic content . At the end of the experiments a full mass balance was carried by break ing down the columns and extract ing any remaining contaminants by shaking to ensure everything was accounted for.